Hello developper puis reduire...a=3(x-2)+5(3-x)......b=x(3+x)-2(x+5).....c=-2(x-7)-2(x²+x)+4(x²+1)....d=2x(-x+5)-x²(1-x)........e=-6x(2x²-3x)-3(x+4x²)-x(-3+4x).............f=1/2(3/2X+1/5°=.......g=-3/5(2/3X+4/3)=......h=7/5(3/2x²-3/7)=........i=-2/5x(3/2X+1/5)=....k=-3/4x²(5/7-3/2x)=

1

Réponses

2014-02-07T16:39:00+01:00
Bonjour,

a = 3(x - 2) + 5(3 - x)
   = 3x - 6 + 15 - 5x
   = -2x + 9

b = x(3 + x) - 2(x + 5)
   = 3x + x² - 2x - 10
   = x² + x - 10

c = -2(x - 7) - 2(x² + x) + 4(x² + 1)
   = -2x + 14 - 2x² - 2x + 4x² + 4
   = 2x² - 4x + 18 
  
d = 2x(-x + 5) - x²(1 - x)
   = -2x² + 10x - x² + x^3
   = x^3 - 3x² + 10x

e = -6x(2x² - 3x) - 3(x + 4x²) - x(-3 + 4x)
   = -12x^3 + 18x² - 3x - 12x² + 3x - 4x²
   = -12x^3 + 2x²

f = 1/2(3/2x + 1/5) 
  = 3/4 x + 1/10

g = -3/5(2/3x + 4/3)
   = - 2/5 x - 4/5

h = 7/5(3/2x² - 3/7)
   = 21/10 x² - 3/5

i = -2/5x(3/2x +1/5)
  = -3/5 x² - 2/25 x

k = -3/4x²(5/7 - 3/2x) 
   = -15/28 x² + 9/8 x^3.